2020
DOI: 10.3390/pathogens9090745
|View full text |Cite
|
Sign up to set email alerts
|

Classical Swine Fever: A Truly Classical Swine Disease

Abstract: Recent reemergence of classical swine fever (CSF) in previous CSF-free areas reminds the veterinary community of this old disease [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Regarding cross-protectivity of CSFV vaccines, it has been shown that the C-strain vaccine and the LPC G1-based vaccines could prevent the circulation of most G1 CSFVs in the world and reduce the incidences of G3.2 CSFV in Korea, G3.3 CSFV in Thailand, and G3.4 CSFV in Japan and Taiwan ( 36 , 37 , 53 ). The tissue-adapted version of the C-stain vaccine Riemser vaccine has also been demonstrated to provide complete protection against G2.1 and G3.3, and G2.1c CSFVs ( 8 , 38 ). However, we have demonstrated herein that hyperimmune serum from CSFV E2 glycoprotein-immunized mice exhibited better neutralizing abilities against homologous CSFV than heterogeneous viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding cross-protectivity of CSFV vaccines, it has been shown that the C-strain vaccine and the LPC G1-based vaccines could prevent the circulation of most G1 CSFVs in the world and reduce the incidences of G3.2 CSFV in Korea, G3.3 CSFV in Thailand, and G3.4 CSFV in Japan and Taiwan ( 36 , 37 , 53 ). The tissue-adapted version of the C-stain vaccine Riemser vaccine has also been demonstrated to provide complete protection against G2.1 and G3.3, and G2.1c CSFVs ( 8 , 38 ). However, we have demonstrated herein that hyperimmune serum from CSFV E2 glycoprotein-immunized mice exhibited better neutralizing abilities against homologous CSFV than heterogeneous viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Even though areas can be declared CSF-free, the re-emergence of CSF and emergence of new sub-genotypes of classical swine fever virus (CSFV) have been reported ( 6 ). In Japan, outbreaks of G2.1d CSFV in pig farms and wild boars in Gifu City in 2018 were re-emerged after 26 years of CSF-free status ( 6 8 ) indicating the difficulty in eradication of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Live attenuated C-strain CSFV vaccines provide complete protection in at least seven days, but the lack of DIVA is problematic for eradication programs in CSF enzootic areas [ 4 ]. Some live attenuated vaccines also carry genuine concerns over their safety, due to the potential of reversion to virulence and recombination with pathogens in the field [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%